2009
DOI: 10.1016/j.jchromb.2009.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Capillary thermal desorption unit for near real-time analysis of VOCs at sub-trace levels. Application to the analysis of environmental air contamination and breath samples

Abstract: Please cite this article as: M. Alonso, M. Castellanos, J. Martín, J.M. Sanchez, Capillary thermal desorption unit for near real-time analysis of VOCs at sub-trace levels. Application to the analysis of environmental air contamination and breath samples, Journal of Chromatography B (2008Chromatography B ( ), doi:10.1016Chromatography B ( /j.jchromb.2009 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 26 publications
(43 reference statements)
1
22
0
Order By: Relevance
“…Toluene and xylenes were chosen because VOC emissions by cigarette smoke are usually dominated by benzene and these compounds [30]. 2,5-dimethylfuran was included as recent studies have showed its strong correlation with smoking status [22,[24][25][26][27][28]. 1,3-butadiene was not evaluated as it has been found that the elimination of this compound from the respiratory tract is fast and cannot be detected at the limits of detection levels of the instrumental method used in this study after 30 minutes of smoking [24].…”
Section: Breath Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Toluene and xylenes were chosen because VOC emissions by cigarette smoke are usually dominated by benzene and these compounds [30]. 2,5-dimethylfuran was included as recent studies have showed its strong correlation with smoking status [22,[24][25][26][27][28]. 1,3-butadiene was not evaluated as it has been found that the elimination of this compound from the respiratory tract is fast and cannot be detected at the limits of detection levels of the instrumental method used in this study after 30 minutes of smoking [24].…”
Section: Breath Analysismentioning
confidence: 99%
“…The microtrap used in this study was specifically developed for the analysis of VOCs in breath samples at ppbv-pptv levels [27]. The device uses a 80-mm-long, 1.35-mm-i.d.…”
Section: Breath Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Benzene represents a compound typically occurring in cigarette smoke and being stored in different body compartments [4,[23][24][25]. In this study, all patients were ex-smokers.…”
Section: Lung Cancer S Kischkel Et Almentioning
confidence: 99%